The Role of Islamic Education in Addressing the Empathy Crisis Among Adolescents in the Social Media Era - Leni Sulistia Ningsih; Rosdialena (Journal Of Psychology, Counseling And Education, 2026)
This study examines the role of Islamic education in addressing the empathy crisis among adolescents in the social media era. The rapid development of digital technology and the widespread use of social media have significantly changed the patterns of social interaction among adolescents, leading to decreased face-to-face communication, increased individualism, cyberbullying, and reduced social sensitivity. Using a qualitative literature review method, this research analyzes scientific journals, books, and prior studies on Islamic education, character education, and adolescent social behavior. Findings indicate that Islamic education plays a strategic role in fostering empathy through moral education, character development, spiritual guidance, role modeling, and social responsibility programs. Core Islamic values such as rahmah (compassion), ukhuwah (brotherhood), ta’awun (mutual assistance), and ihsan (excellence in conduct) serve as a strong foundation for developing prosocial behavior and emotional intelligence among adolescents. Integrating these values across family, school, and community contexts is essential for effectively addressing empathy decline and nurturing morally responsible adolescents in the digital era.